Cu(i)–SNS complexes for outer-sphere hydroboration and hydrosilylation of carbonyls. Issue 90 (28th October 2019) - Elsby, Matthew R.; Baker, R. Tom
Abstract : Two new NHC–Cu(i )-[κ 2 -SNS] complexes were synthesized to directly compare the bifunctional catalytic activity of a hard amido vs. a soft thiolate donor. Abstract : Two new NHC–Cu(i )-[κ 2 -SNS] complexes were synthesized to directly compare the bifunctional catalytic activity of a hard amido vs. a soft thiolate donor. The Cu thiolate complex catalyzed ketone hydroboration but not hydrosilylation, while the Cu amido complex is a high-performing outer-sphere carbonyl reduction catalyst using boranes and silanes.